A passive dosing method to determine fugacity capacities and partitioning properties of leaves. Issue 10 (22nd September 2016) - Bolinius, Damien Johann; MacLeod, Matthew; McLachlan, Michael S.; Mayer, Philipp; Jahnke, Annika
Abstract : Passive dosing from silicone is used to determine the capacity of leaves to take up chemicals from air and water, which can result in transfer to food webs or soil. Abstract : The capacity of leaves to take up chemicals from the atmosphere and water influences how contaminants are transferred into food webs and soil. We provide a proof of concept of a passive dosing method to measure leaf/polydimethylsiloxane partition ratios ( K leaf/PDMS ) for intact leaves, using polychlorinated biphenyls (PCBs) as model chemicals. Rhododendron leaves held in contact with PCB-loaded PDMS reached between 76 and 99% of equilibrium within 4 days for PCBs 3, 4, 28, 52, 101, 118, 138 and 180. Equilibrium K leaf/PDMS extrapolated from the uptake kinetics measured over 4 days ranged from 0.075 (PCB 180) to 0.371 (PCB 3). The K leaf/PDMS data can readily be converted to fugacity capacities of leaves ( Z leaf ) and subsequently leaf/water or leaf/air partition ratios ( K leaf/water and K leaf/air ) using partitioning data from the literature. Results of our measurements are within the variability observed for plant/air partition ratios ( K plant/air ) found in the literature. Log K leaf/air from this study ranged from 5.00 (PCB 3) to 8.30 (PCB 180) compared to log K plant/air of 3.31 (PCB 3) to 8.88 (PCB 180) found in the literature. The method we describe could provide data to characterize the variability in sorptive capacities of leaves that would improve descriptions of uptake of chemicals by leaves in multimedia fate models.